Understanding Users’ Behavioral Intention to Use the Digital Currency Electronic Payment in China - Wei, Yizhen; Amer Azlan Abdul Jamal; Rosle Mohidin (Human Resource Management Academic Research Society (HRMARS), 2023)
In 2014, the Digital Currency Electronic Payment (or DC/EP) was introduced in China with the goal of improving monetary and financial supervision. Following its initial trial in 2019, the effectiveness and level of acceptance of DC/EP among the people of the Republic of China is yet unknown. On that account, the purpose of this paper is to investigate the factors that drive the behavioral intention to use the DC/EP in China. Using quantitative online survey method, a total of 392 valid responses were received from the people that had used the DC/EP. Data was analysed through structural equation modelling technique using the SMARTPLS 4.0 software. The results suggest that perceived usefulness, perceived ease of use, user's attitude and user's trust are significantly associated with user's behavioral intention to use the DC/EP, and that there is a high acceptance of digital currency in China. Additionally, the results also showed the importance of social influence which significantly influences user’s intention to accept the new technology. The findings of this study serve as part of the theoretical foundation for future research into the deployment of digital currency electronic payment systems.